Structural Transformation and Energy Intensity in Emerging Markets and Developing Economies - Suparta, I. Wayan; Awaluddin, Imam; Nirmala, Tiara; Murwiati, Asih; Wahyudi, Heru; Leny, Sandra Mei (International Journal of Energy Economics and Policy, 2025)
Improving energy efficiency is one of the key pillars in the transition to a low-carbon economy and sustainable development. However, amidst increasing urbanisation, labour force growth and renewable energy adoption, energy intensity in emerging markets and developing economies (EMDEs) is still showing a stagnant trend. This indicates the existence of non-sectoral structural dynamics that have not been fully identified in previous literature. This research is motivated by the urgent need to quantitatively examine how demographic transformation and clean energy affect national energy efficiency in Emerging Markets and Developing Economies. This study aims to analyse the influence of urban population (% of total population), labour force participation rate (% of working age population), and renewable energy consumption (% of total final energy consumption) on the energy intensity level of primary energy in 25 EMDEs countries over the period 2017-2021. Based on previous theoretical studies and empirical trends, it is hypothesised that urbanisation and renewable energy consumption reduce energy intensity, while labour force participation tends to increase energy intensity if not accompanied by sectoral and technological reforms. The research methodology uses panel data regression approach with Fixed Effect Model. The analysis shows that partially, urban population and renewable energy consumption have a negative and significant effect on energy intensity, while labour force participation rate shows a positive and significant effect. Simultaneously, the three variables have a significant effect on energy intensity. The coefficient of determination (R2) of 0.991589 indicates that 99.15% of the variation in energy intensity can be explained by the variation in the three independent variables. This finding confirms the importance of policy formulation that integrates demographic structural transformation and renewable energy transition to sustainably reduce energy intensity in EMDEs countries.